The Influence Of Budget Participation, Information Asymmetry And Organizational Commitment In The Preparation Of Apbdes To Budgetary Slack - Anthon S.Y. Kerihi; Yohanes Simon Key; Maria Elerina Douk Tunti (Green Publisher Indonesia, 2022)
This research aims to find out the influence of budget participation, information asymmetry and organizational commitment in the preparation of APBDes to budgetary salck (Study on Villages in Waigete District, Sikka Regency). This type of research is quantitative research. The sampling technique in this study is purposive sampling using a sample of 9 villages and each village was selected by 5 respondents (village head, village secretary, financial kaur, planning kaur and BPD chairman) so that 45 respondents were obtained. The data collection techniques in this study used questionnaires. The data analysis technique in this study used multiple linear regression analysis. The data sources used are primary data and skunder data. The results of this study showed that 1) budget participation in the preparation of village APBDes in Waigete District, Sikka Regency had no effect on budgetary slack, 2) information asymmetry in the preparation of village APBDes in Waigete District, Sikka Regency had an effect on budgetary slack, 3) organizational commitment in the preparation of village APBDes in Waigete District, Sikka Regency had no effect on budgetary slack and 4) budget participation, Information asymmetry and organizational commitment in the preparation of village APBDes in Waigete District, Sikka Regency jointly affect budgetary slack.